COMMUNITY ADVANCEMENT IN COMMUNITY POLICING WITHIN THE ADDIS ABABA CITY ORGANIZATION - Alehegn (PhD Scholar), Derese Simegnew; (Asso. Prof), Dr.R. Karunakaran; Engida (Asst. Prof), Dr. Bantyergu (The journal of contemporary issues in business and government, 2024)
Community development focuses on improving the quality of life and well-being of individuals and communities. This exploratory study used a descriptive research design and mixed methods research strategy. The study uses primary and secondary data, including questionnaires and interviews with front-line police, intermediate and senior officials, and unpublished documents from verified organizations such as the AAPC. The quantitative approach focuses on the degree to which community policing is applied, while qualitative approaches identify obstacles to successful deployment. This research aimed to provide unbiased descriptions of experiences in natural settings. However, the increase in crime has reduced public confidence and security, leading to low levels of human well-being. The Ethiopian government has worked to identify the root cause of the problem and implement initiatives to ensure smooth operations. Police have involved community participation in problem-solving partnerships, and various community programs have been organized to provide knowledge and skills in handling crime-related cases. This has enhanced community confidence and overall well-being.